Prevalência e fatores associados às lesões elementares em idosos internados - Clóris Regina Blanski Grden; Taís Ivastcheschen; Luciane Patrícia Andreani Cabral; Péricles Martim Reche; Danielle Bordin (Universidade Federal do Ceará, 2019)
Objective to analyze the prevalence and factors associated with elementary lesions in the elderly hospitalized in a teaching hospital.Methods cross-sectional study with 202 elderly people. A sociodemographic and clinical questionnaire and a nursing physical examination were applied. For analysis, Stata software® version 12 was used.Results a total of 176 (87.1%) participants had some elementary lesion. Primary elementary lesions presented significant statistical relationship with age range ≥80 years (p=0.023), respiratory diseases (p=0.029), medical devices (p=0.000), restricted mobility (p=0.001), independence (p=0.006), or need for aid (p=0.007). Secondary elementary lesions were associated with being married (p=0.007), medical devices (p=0.029), and restricted mobility (p=0.012).Conclusion there was high prevalence of elementary lesions in hospitalized elderly and important associated factors. This highlights the importance of nurses to evaluate, identify, and conduct preventive care specific to this population.